Correlation of Serum Ferritin and Cardiac Iron Toxicity with Cardiac Function in Transfusion Dependent Beta-Thalassemia Major Patients - Tubagus Djumhana Atmakusuma; Rajesh Kalwani; Sally Aman Nasution; Cleopas Martin Rumende (Interna Publishing, 2021)
Background: Cardiac iron toxicity is a major cause of mortality in transfusion-dependent beta-thalassemia major patients. The main modality for detecting cardiac iron toxicity is MRI T2* with limited availability. This study aims to obtain iron toxicity profiles in transfusion-dependent beta-thalassemia patients; to see a correlation between iron toxicity and cardiac function. Methods: We conducted a cross-sectional study at the Adult Thalassemia Polyclinic of Cipto Mangunkusumo Hospital, Indonesia from December 2017 to March 2018. We performed the statistical analysis using Pearson/Spearman Test comparing MRI T2* values with ejection fraction and E/A ratio. Results: The median of 4-months mean of ferritin levels was 5130 ng/mL. The mean for cardiac T2* was 24.96 ms. Severe cardiac hemosiderosis (mean cardiac MRI T2* < 10 ms)  occurred in 11.3% of the subjects.  There was weak correlation between serum ferritin with cardiac iron toxicity (r=-0.272, p=0.032) and ejection fraction (r=-0.281, p=0.013). But, there was no correlation between cardiac iron toxicity with ejection fraction and E/A ratio. Conclusion: Serum ferritin correlated weakly with cardiac iron toxicity and cardiac systolic function. Meanwhile, there was no correlation between cardiac iron toxicity with cardiac systolic and diastolic function.